2007
DOI: 10.1073/pnas.0702544104
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B1 mutations in prostate cancer

Abstract: Semaphorins are a large class of secreted or membrane-associated proteins that act as chemotactic cues for cell movement via their transmembrane receptors, plexins. We hypothesized that the function of the semaphorin signaling pathway in the control of cell migration could be harnessed by cancer cells during invasion and metastasis. We now report 13 somatic missense mutations in the cytoplasmic domain of the Plexin-B1 gene. Mutations were found in 89% (8 of 9) of prostate cancer bone metastases, in 41% (7 of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 28 publications
9
91
0
Order By: Relevance
“…For example, plexin-A expression has been observed in ovarian (Syed et al, 2005) and gastric (Zhao et al, 2007) carcinoma, as well as in tumor-derived cells of glioma (Rieger et al, 2003), melanoma, and breast (Castro-Rivera et al, 2008; Castro-Rivera et al, 2004;Kigel et al, 2008) and colon (Nguyen et al, 2006) cancer. The expression of plexin-B1 has been reported in ovarian and prostate cancers (Syed et al, 2005;Wong et al, 2007). In addition, a high frequency of somatic missense mutations in plexin-B1, and its overexpression at the protein level, seems to correlate with increased invasiveness and metastatic progression of prostate tumors (Wong et al, 2007).…”
Section: Expression Of Semaphorin Receptors By Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, plexin-A expression has been observed in ovarian (Syed et al, 2005) and gastric (Zhao et al, 2007) carcinoma, as well as in tumor-derived cells of glioma (Rieger et al, 2003), melanoma, and breast (Castro-Rivera et al, 2008; Castro-Rivera et al, 2004;Kigel et al, 2008) and colon (Nguyen et al, 2006) cancer. The expression of plexin-B1 has been reported in ovarian and prostate cancers (Syed et al, 2005;Wong et al, 2007). In addition, a high frequency of somatic missense mutations in plexin-B1, and its overexpression at the protein level, seems to correlate with increased invasiveness and metastatic progression of prostate tumors (Wong et al, 2007).…”
Section: Expression Of Semaphorin Receptors By Tumor Cellsmentioning
confidence: 99%
“…The expression of plexin-B1 has been reported in ovarian and prostate cancers (Syed et al, 2005;Wong et al, 2007). In addition, a high frequency of somatic missense mutations in plexin-B1, and its overexpression at the protein level, seems to correlate with increased invasiveness and metastatic progression of prostate tumors (Wong et al, 2007). In contrast to these reports, a marked downregulation of plexin-B1 expression has been reported in clear-cell renal carcinoma (Gomez Roman et al, 2008), and loss of plexin-B1 gene expression was found to correlate with poor prognosis in estrogen-receptor-positive breast cancer (Rody et al, 2007).…”
Section: Expression Of Semaphorin Receptors By Tumor Cellsmentioning
confidence: 99%
“…Contrasting findings regarding the expression profile of Sema4D and the plexin-B family in relation to different types of tumours have also been reported. For example, an increased Sema4D and plexin-B1 expression has also been observed in prostate (25)(26)(27), cervical (28), and breast and ovarian cancers (29). A combined effect of increased plexin-B1 along with c-Met was associated with poor cell differentiation and higher lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of cyclin E can be found in Barrett's epithelium and is upregulated in dysplasia and cancer (29,30). Plexins have a role in the regulation of the actin cytoskeleton and can activate changes in extracellular matrix adhesion and motility that contribute to the invasive phenotype in cancer (31). They can also interact with and activate the receptor tyrosine kinases ErbB2 and c-Met (32).…”
Section: Dfmo Modulates Gene Expression In Barrett's Mucosamentioning
confidence: 99%